A Game Map: Object of Copyright and Form of Authority in Eighteenth-Century Britain. Issue Volume 72:Issues 2(2020) (2nd July 2020) - Alexander, Isabella; Martinez, Cristina S.
Abstract: This essay studies in detail—from a legal and aesthetic perspective—an eighteenth-century game map that became the object of a copyright dispute. Thomas Jefferys's Royal Geographical Pastime or the Complete Tour of Europe was only the second geographical game to be produced in Britain. The game was, however, more than a simple pastime for an educated public. The map fed notions of hegemony and carried political messages about the relationships between Britain and her continental neighbours, while at the same time informing attitudes towards education and the role of Enlightenment ideas. The present study is concerned with the historical associations between maps and copyright law against this background. It questions the impact of making incremental changes to, and copying, an existing map on the regular operations of mapmakers, which conferred legitimacy on the maps while also posing legal challenges. These challenges were in turn complicated by the status of the map as an object with diverse functions and meanings.